Piezoelectric interfacial waves in langasite and dilithium tetraborate - DANICKI, E.; LAPRUS, W. (Archives of Acoustics, 1996)
Waves propagating along a perfectly conducting plane embedded in a piezoelectric medium are investigated. Numerical analysis of trigonal langasite (LGS) and cubic dilithium tetraborate (LBO) crystals shows that such waves exist for many orientations of the conducting plane with respect to the crystallographic axes, and for many directions of propagation. The wave velocity is close to that of the slowest shear wave for the same direction, and the piezoelectric coupling coefficient can be as high as 1.65% for LBO and 0.25% for LGS. The conditions of existence, and the properties of the most interesting waves are presented. Expected applications are discussed.